Small and Large Firms over the Business Cycle - Crouzet, Nicolas; Mehrotra, Neil R. (American Economic Review, 2020)
This paper uses new confidential Census data to revisit the relationship between firm size, cyclicality, and financial frictions. First, we find that large firms (the top 1 percent by size) are less cyclically sensitive than the rest. Second, high and rising concentration implies that the higher cyclicality of the bottom 99 percent of firms only has a modest impact on aggregate fluctuations. Third, differences in cyclicality are not simply explained by financing, and in fact appear largely unrelated to proxies for financial strength. We instead provide evidence for an alternative mechanism based on the industry scope of the very largest firms. (JEL D22, E32, G32, L25)